Algunas caracteristicas microclimaticas en un campo de tabaco tapado - Sosa, S.A.=700 1 Perez, E.; Otero, E.; Garcia, R.; Pita, O.
(Es, En)
Ilus., 11 ref.
Keywords: NICOTIANA TABACUM; FACTORES CLIMATICOS; MICROCLIMA; PLANTACIONEs; CULTIVO PROTEGIDO; CUBA